2022
DOI: 10.1093/plcell/koac236
|View full text |Cite
|
Sign up to set email alerts
|

TANDEM ZINC-FINGER/PLUS3 regulates phytochrome B abundance and signaling to fine-tune hypocotyl growth

Abstract: TANDEM ZINC-FINGER/PLUS3 (TZP) is a transcriptional regulator that acts at the crossroads of light and photoperiodic signaling. Here, we unveil a role for TZP in fine-tuning hypocotyl elongation under red light and long-day conditions. We provide genetic evidence for a synergistic action between TZP and PHOTOPERIODIC CONTROL OF HYPOCOTYL 1 (PCH1) in regulating the protein abundance of PHYTOCHROME INTERACTING FACTOR 4 (PIF4) and downstream gene expression in response to red light and long days. Furthermore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…Many positive factors promote light responses by enhancing phyB itself rather than promoting light responses downstream of phyB, while the majority of negative factors primarily suppress light responses downstream of phyB. Among the positive factors, PCH1/PCHL stabilize Pfr by suppressing the thermal reversion to Pr (Enderle et al ., 2017; Huang et al ., 2019), while TZP stabilizes phyB (Fang et al ., 2022). PhyC/E increase the overall level of phyB dimers by heterodimerizing (Clack et al ., 2009).…”
Section: Phytochrome B Photobody Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many positive factors promote light responses by enhancing phyB itself rather than promoting light responses downstream of phyB, while the majority of negative factors primarily suppress light responses downstream of phyB. Among the positive factors, PCH1/PCHL stabilize Pfr by suppressing the thermal reversion to Pr (Enderle et al ., 2017; Huang et al ., 2019), while TZP stabilizes phyB (Fang et al ., 2022). PhyC/E increase the overall level of phyB dimers by heterodimerizing (Clack et al ., 2009).…”
Section: Phytochrome B Photobody Componentsmentioning
confidence: 99%
“…Since phyB Y276H has a red light‐absorbing Pr‐like spectral property and forms photobodies that cannot be disassembled by a far‐red pulse (Su & Lagarias, 2007), the reduced number of phyB Y276H photobodies in the pch1 mutant implies that PCH1 enhances the formation of phyB photobody through other means as well. Similarly, both the hmr and tzp mutations decrease the size of phyB Y276H photobodies, with a concomitant increase in the number of small photobodies (Chen et al ., 2010; Fang et al ., 2022). Intriguingly, ELF3 and PIF7 have the ability to form molecular condensates in vitro by themselves (Jung et al ., 2020; Xie et al ., 2023), while COP1/SPA1 can also form their own nuclear bodies in animal cells (Yang et al ., 2018; Liu et al ., 2022).…”
Section: Phytochrome B Photobody Componentsmentioning
confidence: 99%
“…PB formation correlates with PHYB responses and has been considered necessary in PHYB signaling 12 14 . PBs were proposed to participate in the PHYB-mediated degradation of PIF1 and PIF3 34 , 38 40 , sequestration of PIF7 41 , 42 , and transcriptional regulation by TANDEM ZINC-FINGER/PLUS (TZP) 43 , 44 . Further supporting the functional role of PBs in PHYB signaling, recent proteomics studies have revealed that many PHYB signaling components reside in PBs, particularly those that interact directly or indirectly with PHYB 45 , 46 .…”
Section: Introductionmentioning
confidence: 99%